Perancangan Aplikasi Sistem Inventori Berbasis Web Dengan Metode Waterfall (Studi Kasus: PT. Kreatifindo Jaya Bersama) - Destin Mahardika Wijayanti; Sartika Lina Mulani Sitio (CV. Multi Kreasi Media, 2023)
PT. Kreatifindo Jaya Bersama is a company engaged in manufacturing Plastic Pallets and also Trading for several products such as Container Boxes, Forklifts and Rack Systems. In carrying out stock control using a semi-computerized system with Microsoft Excel for data processing. The system used is felt to be quite slow in presenting stock reports per item owned by the company and the results are often inaccurate, causing a shortage of stock in the company when sales decline. This causes customer disappointment because the type of goods ordered does not exist, or losses to the company due to stockpiling in warehouses that are prone to damage. The application of internet technology can be used to manage information about seminar activities. Some of the steps needed to create system information are analysis of system requirements, system design, programming or system implementation and testing. The system was developed using the Codeigniter 3.0.6 framework with the PHP programming language and MySQL database as data storage.